Bioresorbable scaffold implantation in STEMI patients: 5 years imaging subanalysis of PRAGUE-19 study - Kočka, Viktor; Toušek, Petr; Kozel, Martin; Buono, Andrea; Hajšl, Martin; Lisa, Libor; Buděšínský, Tomáš; Malý, Martin; Widimský, Petr (Journal of translational medicine, 2020)
BACKGROUND: Bioresorbable scaffold (BRS) AbsorbTM clinical use has been stopped due to higher rate of device thrombosis. Scaffold struts persist longer than 2 years in the vessel wall. Second generation devices are being developed. This study evaluates long-term invasive imaging in STEMI patients. METHODS: PRAGUE-19 study is an academic study enrolling consecutive STEMI patients with intention to implant AbsorbTM BRS. A total of 83 STEMI patients between December 2012 and March 2014 fulfilled entry criteria. Coronary angiography and optical coherence tomography at 5 year follow-up was performed in 25 patients. RESULTS: Primary combined clinical endpoint (death, myocardial infarction or target vessel revascularization) occurred in 12.6% during the five-year follow-up with overall mortality 6.3%. Definite scaffold thrombosis occurred in 2 patients in the early phase after BRS implantation. Quantitative coronary angiography after 5 years demonstrated low late lumen loss of 0.11 ± 0.35 mm with binary restenosis rate of 0%. Optical coherence tomography demonstrated complete resorption of scaffold struts and mean lumen diameter of 3.25 ± 0.30 and 3.22 ± 0.49 (P = 0.73) at baseline and after 5 years, respectively. Three patients developed small coronary artery aneurysm in the treated segment. CONCLUSION: Invasive imaging results 5 years after BRS implantation in STEMI showed complete resorption of scaffold struts and stable lumen vessel diameter. Trial registration ISRCTN43696201 (retrospectivelly registred, June 7th, 2019). https://www.isrctn.com/ISRCTN43696201.
Keywords: infarkt myokardu s elevacemi ST úseků; protézy - design; Percutaneous Coronary Intervention; Prosthesis Design; vstřebatelné implantáty; Absorbable Implants; lidé; Coronary Angiography; Humans; ST Elevation Myocardial Infarction; stenty uvolňující léky; koronární angiografie; Drug-Eluting Stents; koronární angioplastika; výsledek terapie; Treatment Outcome